KEDUDUKAN HASIL ANALISIS PUSAT PEMERIKSA ANALISIS TRANSAKSI KEUANGAN DALAM PEMBUKTIAN TINDAK PIDANA PENCUCIAN UANG - Renalmon Josua Serra; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The crime of money laundering (TPPU) is the act of hiding or disguising moneyobtained from illegal sources into legal (legal) money. The act is done with the aim tocomplicate law enforcement officers in investigating the origin of money / wealth. lawenforcement officers find it difficult to prove the existence of TPPU because thedocuments found do not lead to the deeds as specified in article 2 of Law no. 8 Year2010 on the Prevention and Eradication of Money Laundering Crime (PP-TPPU). Thisis an obstacle in the process of investigation conducted by law enforcement officers tofollow up the case. The problem of this thesis is the first, concerning the position ofPPATK (Center for Financial Transaction Reporting and Analysis) in money launderingcrime related to Money Laundering crime seen from Law No. 8 Year 2010. Second, thestrength of result of analysis from PPATK and validity of analysis in the Criminal Codeand Criminal Procedure Code. Thirdly, the PPATK effort in proving the data resultfrom money launderers in Indonesia. This type of research can be classified in the typeof normative juridical research, because in this study the author discusses the principlesof law, legal system, the level of legal synchronization, legal history and comparativelaw and to provide a complete and clear picture of the problems examined by the author.This research is done by normative method, data source used with cases that exist ininternet and literature studyKeywords: Crime, Money Laundering, Law Enforcement